Home Insurance and Gurantee Corporation (HIGC) - Larosa, Luningning (Animo Repository, 1996)
The purpose of the group for conducting a Management Information System (MIS) on Home Insurance and Guarantee Corporation (HIGC) is to help the corporation widen their horizons in terms of their field and technology. Another purpose is for the group to apply what we have learned in MIS-ONE class such as conducting an MIS study in a certain organization hus, unmasking the weak points of the existing systems and probable problems that might or occurred in the process of studying. The group focused on the two departments under the staff of the office of Executive Vice-President and General Manager. These two departments are Personnel and Inventory Department. Another focus is on the Payroll Department which is under the Finance Group. The main objective of the study team is to analyze and create a 3-year MIS Plan in the three departments (Payroll, Personnel, Inventory) selected in HIGC that will suitable of great benefit in the attainment of the objectives of the company.